Occult Breast Lobular Carcinoma with Numerous Circulating Tumor Cells in Peripheral Blood - Kanako Ogura; Maki Amano; Toshiharu Matsumoto; Asumi Sakaguchi; Taijiro Kosaka; Toshiaki Kitabatake; Kuniaki Kojima (Hindawi Limited, 2015)
We experienced a very rare case of occult breast lobular carcinoma with numerous circulating tumor cells in peripheral blood. The diagnosis was very difficult because there were no symptoms of breast cancer and the preceding chief complaints such as general fatigue and weight loss or abnormality of peripheral blood findings were suggestive of a hematological disease. We could make a correct diagnosis of this case by checking the findings of complete blood count and bone marrow biopsy at the same time using immunohistochemistry.